Entanglement over the rainbow. (1st June 2015) - Ramírez, Giovanni; Rodríguez-Laguna, Javier; Sierra, Germán
Abstract: In one dimension the area law for the entanglement entropy is violated maximally by the ground state of a strongly inhomogeneous spin chain, the so called concentric singlet phase (CSP), that looks like a rainbow connecting the two halves of the chain. In this paper we show that, in the weak inhomogeneity limit, the rainbow state is a thermo field double of a conformal field theory with a temperature proportional to the inhomogeneity parameter. This result suggests some relation of the CSP with black holes. Finally, we propose an extension of the model to higher dimensions.